Clinical signs and symptoms of toxic serum digoxin levels in neonates - Mehmet Mutlu; Yakup Aslan; Şebnem Kader; Filiz Aktürk-Acar; Embiya Dilber (The Turkish Journal of Pediatrics)
Digoxin is widely used in the treatment of congestive heart failure and some arrhythmias. Digoxin toxicity may occur easily because digoxin has a narrow therapeutic index. This retrospective study was conducted to evaluate the clinical signs and symptoms of toxic serum digoxin levels in neonates. Medical reports of the neonates who had serum digoxin concentrations > 2 nanogram/milliliter (ng/ml) were reviewed in terms of patient demographics, serum digoxin concentrations, signs and symptoms of digoxin toxicity, serum digoxin and electrolyte levels, renal function tests, electrocardiograms, echocardiography, and treatments applied. Digoxin toxic levels were identified in the 13 neonates. Of the 13 neonates with digoxin toxic level, 9 (69%) were term and 8 (62%) were female. Twenty-three percent (3/13) of newborn infants were symptomatic. Symptomatic patients had statistically significantly higher serum digoxin levels, at 7.76±2.76 (5.4-10.8) ng/ml, than asymptomatic patients, at 3.31±1.09 (2.02-4.95) (p=0.036). Symptoms related to toxic digoxin levels were observed in the three neonates with plasma digoxin levels > 5 ng/ml. Gastrointestinal and central nervous system symptoms were the major clinic findings. Despite high digoxin levels, no digoxin-related arrhythmia was observed on electrocardiography, other than sinus bradycardia. Two premature neonates were treated with digoxin-specific antibody Fab fragments (DigiFab®) and hypokalemia developed in both of them. Our data suggests that symptoms related with digoxin toxic levels were observed in neonates with plasma digoxin levels > 5 ng/ml. Serum digoxin levels should be measured in case of signs and symptoms of digoxin toxicity or risk factors for such toxicity.